2009
DOI: 10.1021/cg9008569
|View full text |Cite
|
Sign up to set email alerts
|

Anthracene-Arrangement-Dependent Emissions of Crystals of 9-Anthrylpyrazole Derivatives

Abstract: We have designed and synthesized a series of 9-anthrylpyrazole derivatives 1,4-bis(3-(9-anthryl)-1-pyrazolylmethyl)benzene (1), 1-(3-(9-anthryl)-1-pyrazolylmethyl)-4-(5-(9-anthryl)-1-pyrazolylmethyl)benzene (2), 1,4-bis(3-(9-anthryl)-1-pyrazolyl)benzene (3), and 1-(3-(9-anthryl)-1-pyrazolyl)-4-(5-(9-anthryl)-1-pyrazolyl)benzene (4). All compounds formed two types of crystals that exhibited anthracene-arrangement-dependent emission colors. For instance, crystal 1a with strong π-overlap between anthracene moieti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
60
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(64 citation statements)
references
References 54 publications
4
60
0
Order By: Relevance
“…Generally, an increased planarity increases the Φ F , and more intermolecular π–π interactions lead to a lower Φ F 20a. 28 The N form of 1 , with fewer head‐to‐tail π–π interactions, is more planar than the B form, and thus the former has a higher Φ F (0.44) than that of the latter (0.20). Furthermore, complex 2 , which has multiple π–π interactions and receives contributions from both face‐to‐face and head‐to‐tail packing, displays the lowest Φ F value (0.10) of all the complexes reported in the present system.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, an increased planarity increases the Φ F , and more intermolecular π–π interactions lead to a lower Φ F 20a. 28 The N form of 1 , with fewer head‐to‐tail π–π interactions, is more planar than the B form, and thus the former has a higher Φ F (0.44) than that of the latter (0.20). Furthermore, complex 2 , which has multiple π–π interactions and receives contributions from both face‐to‐face and head‐to‐tail packing, displays the lowest Φ F value (0.10) of all the complexes reported in the present system.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, dimeric stacks of polyaromatic molecules have received considerable attention, because their structures sometimes exhibit intriguing fluorescence behavior derived from the formation of excimers. [8] To exploit anew class of polyaromatic solids with agreater emissive ability,wedesigned aV -shaped polyaromatic compound bearing bulky substituents on the convex side to engineer 1) the dimeric stack of the bent polyaromatic frameworks (Figure 1c)a nd 2) the layered arrays of the polyaromatic dimers through intermolecular interactions between the substituents.H ere we report the unusual emission behavior of V-shaped bisanthracene derivative 1 with three butyl groups (Figure 1d)i nt he solid state. [8] To exploit anew class of polyaromatic solids with agreater emissive ability,wedesigned aV -shaped polyaromatic compound bearing bulky substituents on the convex side to engineer 1) the dimeric stack of the bent polyaromatic frameworks (Figure 1c)a nd 2) the layered arrays of the polyaromatic dimers through intermolecular interactions between the substituents.H ere we report the unusual emission behavior of V-shaped bisanthracene derivative 1 with three butyl groups (Figure 1d)i nt he solid state.…”
mentioning
confidence: 99%
“…[20] Another important approach involves tuning the packing and arrangement of molecules in the solid state. [21] Tohnai and co‐workers recently noted the significance of dimensionality, as well as the rigidity, of molecular arrangements in their study on the control of fluorescence in organic salts of anthracene‐2,6‐disulfonic acid with alkyl amines. [22] We also investigated the fluorescence properties of several alkyl‐substituted anthracenes ( 18 – 23 ) and found that some of these derivatives exhibited high quantum yields in the solid state (Table 1).…”
Section: Fluorescence Properties Of Alkyl‐substituted Tetracenesmentioning
confidence: 99%